Pretreatments applied to microalgae residues to enhance anaerobic digestion - Rodrigues, M.P. (2020)
Poster apresentado em WASTES: Solutions, Treatments and Opportunities. 5th International Conference, September 4th - 6th, Almada/Caparica, Portugal